Sistem Mailtracking Dengan Digital Signature - - STMIK AUB Surakarta, Wisnu Wendanto (APMMI - Asosiasi Profesi Multimedia Indonesia, 2015)
Abstract - Mailing administration system is often called as mailtracking system is a system used for document management such as the disposition letter, official letters, filing, reporting, and so forth. The documents are in addition to functioning as a means of communication between personal, unit, also serves as formal evidence of activities that can be accounted for (legal aspects). On the other hand, the management and archiving is often a problem that is quite time-consuming and labor intensive. Document traffic can become very large and require a filing system that is also greater (aspect of efficiency).This research aims to develop an application system mailtracking using the digital signature for data security are expected to support the process of routing and monitoring letter so as to create legitimacy and efficiency in the administration of the correspondence and facilitate in management of the environment regular mailing in STMIK-AUB Surakarta. In this research the data entered is sending one or more to generate the or more digital signature to the letter. Then the letter, the digital signature and the message digest are sent to one or more recipients. After that the recipient will verify if the result of the verification is valid, it means that the letter is valid and the sender of the letter is true. Conversely, if the results are not valid means of the letter or sending unauthorized and not the actual sender of the letter.Keyword : mailtracking, data security, digital signatureÂ Abstrak - sistem administrasi Mailing sering disebut sebagai sistem pelacakan mail sistem yang digunakan untuk manajemen dokumen sepertisuratdisposisi, surat-surat resmi, pengajuan, pelaporan, dan sebagainya. Dokumen-dokumen yang selain berfungsi sebagai sarana komunikasi antara pribadi, unit, juga berfungsi sebagai bukti formal kegiatan yang dapat dipertanggungjawabkan (aspek hukum). Di sisi lain, manajemen dan pengarsipan sering merupakan masalah yang cukup memakan waktu dan tenaga. Dokumen lalu lintas dapat menjadi sangat besar dan memerlukan sistem pengarsipan yang juga lebih besar (aspek efisiensi).Penelitian ini bertujuan untuk mengembangkan pelacakan email sistem aplikasi menggunakan tanda tangan digital untuk keamanan data diharapkan untuk mendukung proses routing dan pemantauan surat sehingga tercipta legitimasi dan efisiensi dalam administrasi surat menyurat dan memudahkan dalam pengelolaan lingkungan mailing biasa di STMIK-AUB Surakarta. Dalam penelitian ini data yang dimasukkan mengirimkan satu atau lebih untuk menghasilkan atau tanda tangan digital lebih untuksuratitu. Kemudiansurat, tanda tangan digital dan message digest dikirim ke satu atau lebih penerima. Setelah itu penerima akan memverifikasi jika hasil verifikasi tersebut valid, itu berarti bahwasurattersebut valid dan pengirimsuratitu benar. Sebaliknya, jika hasilnya tidak berarti sahsuratatau mengirim sah dan tidak pengirim sebenarnya darisuratitu.Kata Kunci: mailtracking, keamanan data, tanda tangan digital